Collision free control of variable length hyper redundant robot manipulator - Jamali, Annisa; Khan, Md. Raisuddin; Osman, M. Shahril; Rahman, Md. Mozasser; Ashari, Muhd Fadzli; Jamaludin, Mohd Syahmi; Junaidi, Ervina (Trans Tech Publications Ltd., Switzerland, 2014)
Hyper-redundant robot (HRR) manipulators are useful at navigating convoluted paths, but conventionally complicated to control. The control of a hyper-redundant manipulator is complex due to its redundancy. In this paper, a simple but effective control algorithm for obstacle avoidance is proposed. The algorithm derives a collision free path around known obstacles so that the end-effector of a variable length hyper redundant robot (VHRR) is able to reach the target location following the path without hitting the obstacles. The algorithm can be grouped into two tasks to drive the end-effector along the collision free trajectories: first, solve the inverse kinematics without disregarding the existence of obstacles in the system; and second, fit the manipulator to the respective prescribe trajectories. This method has the capability to allow VHRR maneuver within its workspace without penetrating to the neighboring obstruction. Further, this method is very effective in the sense that it forms a nice coil profile avoiding zig-zag configuration, and thus eliminates sharp turn on the robot. The performance of a VHRR was tested through simulation to demonstrate the effectiveness of the proposed method. The approach succeeded in delivering the path that avoids obstacle.